Izbrana dela Slovenskih Avtorjev iz zbirk Moderne Galerije. (Ljubljana : Moderna Galerija, 1991)
Jakopic, Rihard ; Tratnik, Fran ; Jakac, Bozidar ; Kralj, Tone ; Vidmar, Nande ; Pilon, Veno ; Cargo, Ivan ; Dolinar, Lojze ; Kralj, France ; etc.
boek
Keywords: Slovenië